Prospects for fabrication of artificial human tissues and organs based on 3D bioprinting - D. V. Bulgin; A. L. Kovtun; I. V. Reshetov; E. Yu. Radomskaya (Вестник трансплантологии и искусственных органов)
Three-dimensional (3D) printing is a method of creating a material object layer-by-layer in space from a virtual, mathematical model. 3D printing is based on additive technologies – a step-by-step formation of a structure by adding material to the base. 3D bioprinting is the fabrication of functional biological structures that mimic human organs and tissues. Analysis of scientific publications showed that in the near future, viable and fully functional artificial copies of individual human organs and tissues can be obtained.